PEMIKIRAN TAFSIR TUAN GURU HAJI ISMAIL BIN UMAR DALAM KITAB MAWAQIF AL-MARJAN - Syed Najihuddin Syed Hassan; Zamrie Ibrahim@ Musa; Ahmad Kamel Mohamed; Idi Bin Hamdi; Abdulloh Salaeh (Journal of Islamic, Social, Economics and Development, 2022)
The Malay Islamic book in Pattani is a heritage of knowledge in the religious field produced by a Malay figure who became a symbol of their scholarship. It reflects the philosophy and identity of the Malay nation and the religious values that support their lives. Among the books whose discoveries have just been revealed to the general public is Mawaqif Al-Marjan, a work of interpretation produced by Tuan Guru Haji Ismail Bin Umar. This book of interpretation is very significant in the context of the study of interpretation and description of the verses of Mutasyabihat and muhakamat verses. However, this study only introduces Mawaqif Al-Marjan because of its approach to interpreting the verses of mutasyabihat which will enlighten the community in a simple way compared to other interpretations such as tafsir nurul ihsan which contains a consensus interpretation that is closer to the concept Translation of Tafsiryyah, stories and others. This style of interpretation is analytically justifying the study of the interpretation approach applied by Tuan Guru Haji Ismail Bin Umar and some aspects of his interpretation. The method of content analysis of the book Mawaqif Al-Marjan to obtain data, then analyzed bibliographically. The findings of the study show that the interpretation approach written by Tuan Guru Haji Ismail conforms to the interpretation approach applied by scholars, which is based on interpretation according to the views of the Salaf and Khalaf. However, this study finds the interpretation approach according to the Salaf and Khalaf view is more clear in this book. The aspects of thinking highlighted by Tuan Guru Haji in the interpretation of the Qur'an are also relevant to the local community, especially when interpreting the verses related to the verses relating to the attributes of God and creation and others. The study found that Mawaqif Al-Marjan's book is an authentic interpretation that is considered as a work and reference that contains value and becomes an important source in Islamic knowledge.